Systematic Review and Meta‐Analysis Suggest Strength Training and Workplace Modifications May Reduce Neck Pain in Office Workers. - Frutiger, Martin; Borotkanics, Robert (Pain Practice, 2021)
Objective: Neck pain is a burdensome musculoskeletal disorder in office workers. Workplace interventions aim to prevent and minimize the effect of neck pain and improve work quality. However, the summed effect of workplace interventions on neck pain in office workers remains unclear. This systematic review with meta‐analysis and meta‐regression evaluated the summed effect of workplace interventions on neck pain in office workers. Methods: We searched 7 electronic databases to January 2020 for randomized clinical trials. We selected studies, independently extracted data, and assessed risk of bias. Meta‐analyses were carried out along with normalized trend plots. Results: Twenty‐nine trials, including 8 of high quality, met our inclusion criteria. Normalized trend plots indicate that neck strengthening demonstrated the sharpest decrease in pain scores. The results of pre‐ and post‐outcome measurement of the effect of activity performance and workplace modification showed significant improvements in self‐reported neck pain (P ≤ 0.001). Meta‐regression was used to evaluate the effect of time, but it was not significant. Conclusions: There is low‐quality evidence that neck strengthening and tailored workstation modifications are effective at reducing neck pain in office workers. Further high‐quality research methodology, including clinicians, is important to evaluate this summed effect.